Spiritual Wellbeing as a Mediator between Stress and Hope in Adolescents: Evidence from a Structural Equation Model - Popescu, Andreea; Mwangi, Grace (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to examine the mediating role of spiritual wellbeing in the relationship between stress and hope among adolescents. Methods and Materials: A descriptive correlational design was employed with a sample of 442 adolescents recruited from secondary schools in Kenya, determined using Krejcie and Morgan’s sampling table. Data were collected using the Perceived Stress Scale (PSS-10), the Spiritual Well-Being Scale (SWBS), and the Children’s Hope Scale (CHS). Statistical analyses were conducted using SPSS version 27 for descriptive statistics and Pearson correlations, while mediation was tested using structural equation modeling (SEM) in AMOS version 21. Model fit was assessed with χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices. Findings: Results indicated that stress was significantly and negatively associated with both hope (r = –.39, p < .001) and spiritual wellbeing (r = –.46, p < .001), while spiritual wellbeing was strongly and positively correlated with hope (r = .53, p < .001). SEM results confirmed good model fit (χ² = 118.47, df = 62, χ²/df = 1.91, GFI = 0.94, AGFI = 0.91, CFI = 0.97, TLI = 0.96, RMSEA = 0.045). Path coefficients revealed that stress directly predicted hope (β = –.21, p < .001) and negatively influenced spiritual wellbeing (β = –.42, p < .001), while spiritual wellbeing positively predicted hope (β = .38, p < .001). Mediation analysis demonstrated a significant indirect effect of stress on hope through spiritual wellbeing (β = –.16, p = .002), confirming partial mediation. Conclusion: The study concludes that spiritual wellbeing plays a significant mediating role in the relationship between stress and hope in adolescents. Strengthening spiritual wellbeing may buffer the detrimental effects of stress and foster greater optimism and resilience among youth.